A Review on Pharmaceutical and Bio-Allied Applications of Infrared Spectroscopy - Muskan; Chopra, Bhawna; Bhardwaj, Sakshi; Dhingra, Ashwani K. (Drug Metabolism and Bioanalysis Letters, 2025)
Infrared spectroscopy has emerged as a powerful analytical technique with diverse applications in the pharmaceutical and bio-allied domains. This article provides an in-depth exploration of the method's utility in pharmaceutical applications, including identification, moisture content determination, and assay of pharmaceutical compounds. Additionally, it delves into the extensive role of infrared spectroscopy in bio-allied research, encompassing the investigation of structural arrangements, interactions, mobility, and dynamics of biomolecules. In the realm of pharmaceuticals, infrared spectroscopy stands as a reliable tool for the identification of compounds, ensuring the authenticity and quality control of drug formulations. The capacity to measure moisture content is crucial in ensuring the stability and efficacy of medicinal goods. Furthermore, the assay of pharmaceutical compounds by infrared spectroscopy offers a rapid and precise means of quantifying active ingredients, supporting the development and production of pharmaceutical formulations. In the bio-allied field, the versatility of infrared spectroscopy becomes evident in its contribution to understanding the intricate details of biomolecular structures and interactions. The method plays a pivotal role in investigating the structural arrangements of macromolecules, shedding light on the complexities of biological systems. Additionally, infrared spectroscopy facilitates the assessment of body fluids, enabling non-invasive diagnostics and monitoring of health conditions. The article also explores the application of infrared spectroscopy in the analysis of blood, providing valuable insights into hematological parameters and contributing to diagnostic methodologies. The method's wide-ranging influence on healthcare and forensic sciences is demonstrated by its promise in cancer detection, forensic investigations, and hematological illness monitoring.
Keywords: non-invasive diagnostics